The development of studies on black entrepreneurship and afro entrepreneurship in Brazil (Research, Society and Development, 2025)
Black Entrepreneurship, or Afro-entrepreneurship, can be defined as the niche of entrepreneurs who self-declare as black, as their color/race identification, regardless of the type of product or service they offer. Furthermore, it could also be a group of black entrepreneurs who offer products and services related to the afro-Brazilian identity, aimed at black consumers. Brazil is the country with the largest black population outside the African continent and therefore has a special interest in the topic. The aim of this study was to map the bibliography on black entrepreneurship in Brazil, creating an overview of the main findings, discussions and gaps. This is an integrative bibliographic analysis that results of a systematic search for the topic using pre-defined keywords according to readings of published scientific literature. Twenty-three articles were identified and analyzed. Despite the gaps in the literature related to black entrepreneurship and afro-entrepreneurship, the analysis shows that there is already some basis for discussing specific public policies focusing on the difficulties observed in this segment of entrepreneurs. It was concluded that studies that have a theoretical depth of impact measurement of afro-entrepreneurship are an opportunity as a field of research, as well as a phenomenon to be studied and highlighted in academia and scientific media, in order to promote a dialogue on the topic and advance proposals for effective strategies to promote black entrepreneurship and afro-entrepreneurship in Brazil.